2020
DOI: 10.1039/d0an00818d
|View full text |Cite
|
Sign up to set email alerts
|

Infrared matrix-assisted laser desorption electrospray ionization (IR-MALDESI) mass spectrometry imaging analysis of endogenous metabolites in cherry tomatoes

Abstract: We report the spatially resolved metabolic profiling of cherry tomatoes using infrared matrix-assisted laser desorption electrospray ionization (IR-MALDESI); an ambient mass spectrometry imaging (MSI) technique that requires no sample derivatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…During the analysis of cherry tomatoes performed earlier, 15 several key metabolites were discovered using the MSiCorrelation tool in MSiReader. 48 MSiCorrelation does not rely on a database for identification, but rather returns the m/z signals that have similar abundance distributions to a reference m/z of interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the analysis of cherry tomatoes performed earlier, 15 several key metabolites were discovered using the MSiCorrelation tool in MSiReader. 48 MSiCorrelation does not rely on a database for identification, but rather returns the m/z signals that have similar abundance distributions to a reference m/z of interest.…”
Section: Resultsmentioning
confidence: 99%
“…14 Due to the post-desorption ESI of IR-MALDESI, most analytes are observed as protonated and sodiated species and other such even-electron ions. However, during a recent IR-MALDESI analysis of tomatoes, 15 the radical cationization of carotenoids was observed, ostensibly the first time for the technique.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that the phenolic content of the cherry tomatoes per unit weight is 3–4 times greater than reported values for large-sized tomatoes and that lycopene showed strong activity against cervical carcinoma and lung cancer cells. Bagley et al [ 19 ] carried out a metabolomic analysis of commercial cherry tomatoes using infrared matrix-assisted laser desorption electrospray ionization (IR-M ALDESI) mass spectrometry imaging analysis. The results revealed the presence of 1626 unique compounds that included new cyanogenic glycosides, glucosinolates, and lignans.…”
Section: Discussionmentioning
confidence: 99%
“… 163 Agtuca et al explored the metabolic asymmetry between infected and noninfected soybean nodules with LAESI where elevated fatty acid, purine, and lipid levels occurred as a result of Bradyrhizobium japonicum infection. 164 The Muddiman group used ice matrices to increase lipid yields, 165 explored dynamic neurotransmitter imaging, 166 used IR-MALDESI for imaging metabolomics in plant and mammalian samples, 167 , 168 and coupled a drift tube for ion mobility direct collision cross section (CCS) measurements from several tissue types. 169 Most recently, cell-to-cell lipid heterogeneity in a dispersed HeLa cell culture was demonstrated by Xing et al with IR-MALDESI.…”
Section: Advances In Single-cell Ms Analysesmentioning
confidence: 99%